2020
DOI: 10.1371/journal.pone.0233102
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of pathogenic attributes in drug resistant Candida auris strains by farnesol

Abstract: Candida auris, a decade old Candida species, has been identified globally as a significant nosocomial multidrug resistant (MDR) pathogen responsible for causing invasive outbreaks. Biofilms and overexpression of efflux pumps such as Major Facilitator Superfamily and ATP Binding Cassette are known to cause multidrug resistance in Candida species, including C. auris. Therefore, targeting these factors may prove an effective approach to combat MDR in C. auris. In this study, 25 clinical isolates of C. auris from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 49 publications
0
37
1
Order By: Relevance
“…Besides, the combination of carvacrol reduced the MIC values of antifungals [17]. Farnesol has shown significant inhibition of planktonic cell growth in C. auris at concentrations ranging from 0.3 to 62.5 mM within 24 h [15,100]. With regards to the in vivo experiments, daily treatment with 75 mM of farnesol decreased the fungal load in an immunosuppressed murine model with disseminated candidiasis, especially in the case of pre-exposed inoculums to farnesol [15].…”
Section: Alternative Treatment Strategies In C Aurismentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the combination of carvacrol reduced the MIC values of antifungals [17]. Farnesol has shown significant inhibition of planktonic cell growth in C. auris at concentrations ranging from 0.3 to 62.5 mM within 24 h [15,100]. With regards to the in vivo experiments, daily treatment with 75 mM of farnesol decreased the fungal load in an immunosuppressed murine model with disseminated candidiasis, especially in the case of pre-exposed inoculums to farnesol [15].…”
Section: Alternative Treatment Strategies In C Aurismentioning
confidence: 99%
“…Both carvacrol and farnesol inhibit cell adherence and biofilm formation, mitigating Candida spp. virulence [15,17,100]. Based on this evidence, phenolic compounds can be said to have an alternative or adjuvant therapeutic potential in conventional treatments to control life-threatening infections caused by C. auris.…”
Section: Alternative Treatment Strategies In C Aurismentioning
confidence: 99%
“…Farnesol, an endogenous quorum sensing molecule, was reported in 2020 by Vartika and Aijaz [130] for its ability to modulate development of biofilms and drug efflux in C. auris. Farnesol also blocked efflux pumps and downregulated biofilm and efflux pump Taken together, these results demonstrated that naturally derivated polymers such as chitosan could be interesting alternatives to conventional antifungals.…”
Section: Small Natural Compoundsmentioning
confidence: 99%
“…One of the promising approaches seems to be synergistic interactions of compounds with antifungals ( Table 2 ). Published data have also focused on the combination therapy as alternative approaches with antifungal drugs open new insights in the management of a global threat of this multidrug-resistant C. auris, as described by Srivastava et al [ 98 ]. In this study, farnesol, a quorum-sensing molecule, suppressed biofilm formation, blocked efflux pumps, and downregulated biofilm and efflux pump-associated genes.…”
Section: Combination Therapies and Novel Treatmentsmentioning
confidence: 99%
“…In this study, farnesol, a quorum-sensing molecule, suppressed biofilm formation, blocked efflux pumps, and downregulated biofilm and efflux pump-associated genes. Farnesol has been indicated as a promising agent to fight a significant nosocomial multidrug-resistant (MDR) pathogen responsible for causing invasive outbreaks [ 98 ]. Similarly, carvacrol, the most active phenolic compound, displayed both antifungal activity with low MIC for clinical isolates of C. auris and a synergistic effect in combination with Flu, AmB, caspofungin, and micafungin, reducing the MIC value of these drugs as well.…”
Section: Combination Therapies and Novel Treatmentsmentioning
confidence: 99%